A Regio‐ and Stereodivergent Synthesis of Homoallylic Amines by a One‐Pot Cooperative‐Catalysis‐Based Allylic Alkylation/Hofmann Rearrangement Strategy. (28th June 2019) - Pearson, Colin M.; Fyfe, James W. B.; Snaddon, Thomas N.
Abstract: Herein, we report a modular synthetic route to linear and branched homoallylic amines that operates through a sequential one‐pot Lewis base/transition‐metal catalyzed allylic alkylation/Hofmann rearrangement strategy. This protocol is operationally trivial, proceeds from simple and easily prepared substrates and catalysts, and enables all aspects of regio‐ and stereoselectivity to be controlled through a conserved experimental protocol. Overall, the high levels of enantio‐, regio‐, and diastereoselectivity obtained, in concert with the ability to access orthogonally protected or free amines, render this a straightforward and effective approach for the preparation of useful enantioenriched homoallylic amines. We have also demonstrated the utility of the products in the context of pharmaceutical synthesis. Abstract : Die regio‐ und stereodivergente Synthese homoallylischer Amine gelang im Eintopf‐Verfahren. Entscheidend hierfür war die Feststellung, dass die erste, katalysierte C‐C‐Bindungsbildung die Regio‐ und Stereoselektivität vollständig kontrolliert. Anschließend wird die C‐N‐Bindung durch In‐situ‐Aminierung und Hofmann‐Umlagerung stereospezifisch geknüpft.